A Procedure Model for Enhancing Ideation in the Collaborative Development of Business Ecosystems - Vorbohle, Christian; Gottschalk, Sebastian; Kundisch, Dennis; Engels, Gregor; Wünderlich, Nancy (Tagungsband der contribution at: 17. Internationale Tagung Wirtschaftsinformatik 2022 (WI))

A Review on Social Media Channel Choice Determinants in Organizations - Arslan, Kader (Proceedings of the 29th European Conference on Information Systems (ECIS 2021))
Keywords: Social media management; Social media; Literature review; Affordances; User behavior; Use culture

A robust cross-efficiency data envelopment analysis model with undesirable outputs - Tavana, Madjid; Toloo, Mehdi; Aghayi, Nazila; Arabmaldar, Aliasghar (Expert Systems with Applications)

A simulation–optimization model for solving flexible flow shop scheduling problems with rework and transportation - Gheisariha, Elmira; Tavana, Madjid; Jolai, Fariborz; Rabiee, Meysam (Mathematics and Computers in Simulation)

A Systematic Review of Organizational Factors Impacting Cloud-based Technology Adoption Using Technology-Organization-Environment Framework - Al Hadwer, Ali; Tavana, Madjid; Gillis, Dan; Rezania, Davar (Internet of Things)

Abweichende steuerliche Verrechnungspreise in der Steuererklärung oder als Ergebnis einer Betriebsprüfung zwischen verschiedenen Staaten - Lorenz, Johannes; Sureth-Sloane, Caren; Diller, Markus

Affordance-Experimentation: Eine Fallstudie zur Entwicklung von Virtual-Reality-Anwendungsfällen im Unternehmenskontext - Fromm, Jennifer; Slawinski, Elena; Mirbabaie, Milad (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Durch technologische Fortschritte in den letzten Jahren ist Virtual Reality erschwinglicher und benutzerfreundlicher geworden, sodass Unternehmen die Einführung der Technologie verstärkt in Betracht ziehen. Ihren Aufschwung erlebte die Technologie jedoch durch die Unterhaltungs- und Spieleindustrie, weshalb sich für Unternehmen die Frage nach sinnvollen Anwendungsfällen stellt. Nach der Affordance-Experimentation-Actualization-Theorie ist insbesondere bei neu aufkommenden Technologien eine Experimentierphase notwendig, um Handlungsmöglichkeiten aufzudecken und daraus Anwendungsfälle zu generieren. Dieser Artikel präsentiert die Ergebnisse einer Fallstudie in einem Unternehmen, das sich während der Studie in der Experimentierphase befand. Durch Interviews mit acht Beschäftigten und einem Vertriebspartner konnten drei Handlungsmöglichkeiten für Virtual Reality im Unternehmenskontext und eine zuvor nicht bekannte Aktivität der Experimentierphase identifiziert werden. Damit erweitert die Studie bisherige Forschung zur Experimentierphase und zeigt Unterschiede im Vergleich zu anderen innovativen Technologien auf, die in vorherigen Studien untersucht wurden. Für Unternehmen bietet die Studie wertvolle Einblicke in die erfolgreiche Gestaltung der Experimentierphase als Vorbereitung auf die Implementierung.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Affording Technology in Crisis Situations: The Occurrence of Rumor Sense-Making Processes - Mirbabaie, Milad; Stieglitz, Stefan; Amojo, Ireti (Journal of Database Management)

An Emerging Theory of Loyalty Program Dynamics - Kim, J. J.; Steinhoff, Lena; Palmatier, R. W. (Journal of the Academy of Marketing Science)

An epsilon-based data envelopment analysis approach for solving performance measurement problems with interval and ordinal dual-role factors - Ebrahimi, Bohlool; Tavana, Madjid; Kleine, Andreas; Dellnitz, Andreas (OR Spectrum)

An integrated and comprehensive fuzzy multicriteria model for supplier selection in digital supply chains - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Amiri, Maghsoud (Sustainable Operations and Computers)

An integrated data envelopment analysis and life cycle assessment method for performance measurement in green construction management - Tavana, Madjid; Izadikhah, Mohammad; Farzipoor Saen, Reza; Zare, Ramin (Environmental Science and Pollution Research)

An integrated fuzzy AHP- fuzzy MULTIMOORA model for supply chain risk-benefit assessment and supplier selection - Tavana, Madjid; Shaabani, Akram; Mansouri Mohammadabadi, Soleyman; Varzgani, Nilofar (International Journal of Systems Science: Operations & Logistics)

An integrated fuzzy framework for analyzing barriers to the implementation of continuous improvement in manufacturing - Tavana, Madjid; Shaabani, Akram; Valaei, Naser (International Journal of Quality & Reliability Management)

An Integrated Fuzzy Goal Programming—Theory of Constraints Model for Production Planning and Optimization - Zare, Habib; Kamali Saraji, Mahyar; Tavana, Madjid; Streimikiene, Dalia; Cavallaro, Fausto (Sustainability)

An integrated fuzzy sustainable supplier evaluation and selection framework for green supply chains in reverse logistics - Tavana, Madjid; Shaabani, Akram; Santos-Arteaga, Francisco J.; Valaei, Naser (Environmental Science and Pollution Research)

An integrated group fuzzy best-worst method and combined compromise solution with Bonferroni functions for supplier selection in reverse supply chains - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Cleaner Logistics and Supply Chain)

An integrated information fusion and grey multi-criteria decision-making framework for sustainable supplier selection - Aslani, Babak; Rabiee, Meysam; Tavana, Madjid (International Journal of Systems Science: Operations & Logistics)

An integrated quality and resilience engineering framework in healthcare with Z-number data envelopment analysis - Tavana, Madjid; Nazari-Shirkouhi, Salman; Farzaneh Kholghabad, Hamidreza (Health Care Management Science)

An inventory-location optimization model for equitable influenza vaccine distribution in developing countries during the COVID-19 pandemic - Rastegar, Mehdi; Tavana, Madjid; Meraj, Afshin; Mina, Hassan (Vaccine)

Anderssein als Ressource: Habitus und Habitusreflexion in der Lehrer*innenbildung - Jenert, Tobias (PraxisForschungLehrer*innenbildung)
Lehrer*innen können dazu beitragen, dass bestehende soziale Ungleichheiten verstärkt oder auch abgebaut werden. Eine wichtige Rolle spielen dabei der sogenannte Habitus der Lehrer*innen und dessen (Nicht-)Passung zur sozialen Herkunft der Schüler*innen. In diesem Text stelle ich die Frage, wie angehende Lehrer*innen im Studium unterstützt werden können, die Bedeutung eigener habitueller Prägungen für das professionelle Handeln als Lehrperson zu reflektieren. Ganz besonders befasse ich mich mit der Rolle der Lehrer*innenbildner*innen bei der Förderung von solchen habitusreflexiven Kompetenzen. Hier spielen das Selbst der Hochschullehrenden und die bildungsbiographischen Erfahrungen, die auf dem Weg in die Hochschule gemacht wurden, eine wichtige Rolle.

Anthropogenic climate change: the impact of the global carbon budget - Redlin, Margarete; Gries, Thomas (Theoretical and Applied Climatology)
Abstract Using time series data for the period 1959–2015, our empirical analysis examines the simultaneous effects of the individual components of the global carbon budget on temperature. Specifically, we explore the possible effects of carbon emissions caused by fossil fuel combustion, cement production, land-use change emissions, and carbon sinks (here in terms of land sink and ocean sink) on climate change. The simultaneous inclusion of carbon emissions and carbon sinks allows us to look at the coexistent and opposing effects of the individual components of the carbon budget and thus provides a holistic perspective from which to explore the relationship between the global carbon budget and global warming. The results reveal a significant positive effect of carbon emissions on temperature for both fossil fuels emissions and emissions from land-use change, confirming previous results concerning carbon dioxide and temperature. Further, while ocean sink does not seem to have a significant effect, we identify a temperature-decreasing effect for land sink.

Are Risk-based Tax Audit Strategies Rewarded? An Analysis of Corporate Tax Avoidance - Eberhartinger, Eva; Safaei, Reyhaneh; Sureth-Sloane, Caren; Wu, Yuchen

Ärger vor der Registereintragung - Bartlitz, David (Juristische Arbeitsblätter (JA))

Artificial intelligence in disease diagnostics: A critical review and classification on the current state of research guiding future direction - Mirbabaie, Milad; Stieglitz, Stefan; Frick, Nicholas R. J. (Health and Technology)
The diagnosis of diseases is decisive for planning proper treatment and ensuring the well-being of patients. Human error hinders accurate diagnostics, as interpreting medical information is a complex and cognitively challenging task. The application of artificial intelligence (AI) can improve the level of diagnostic accuracy and efficiency. While the current literature has examined various approaches to diagnosing various diseases, an overview of fields in which AI has been applied, including their performance aiming to identify emergent digitalized healthcare services, has not yet been adequately realized in extant research. By conducting a critical review, we portray the AI landscape in diagnostics and provide a snapshot to guide future research. This paper extends academia by proposing a research agenda. Practitioners understand the extent to which AI improves diagnostics and how healthcare benefits from it. However, several issues need to be addressed before successful application of AI in disease diagnostics can be achieved.

Artificial intelligence in hospitals: providing a status quo of ethical considerations in academia to guide future research - Mirbabaie, Milad; Hofeditz, Lennart; Frick, Nicholas R. J.; Stieglitz, Stefan (AI & SOCIETY)
Abstract The application of artificial intelligence (AI) in hospitals yields many advantages but also confronts healthcare with ethical questions and challenges. While various disciplines have conducted specific research on the ethical considerations of AI in hospitals, the literature still requires a holistic overview. By conducting a systematic discourse approach highlighted by expert interviews with healthcare specialists, we identified the status quo of interdisciplinary research in academia on ethical considerations and dimensions of AI in hospitals. We found 15 fundamental manuscripts by constructing a citation network for the ethical discourse, and we extracted actionable principles and their relationships. We provide an agenda to guide academia, framed under the principles of biomedical ethics. We provide an understanding of the current ethical discourse of AI in clinical environments, identify where further research is pressingly needed, and discuss additional research questions that should be addressed. We also guide practitioners to acknowledge AI-related benefits in hospitals and to understand the related ethical concerns.

Ausgestaltungs- und Anwendungspotenziale von Virtual und Augmented Reality Technologien im Kontext von Coworking Spaces - Mirbabaie, Milad; Hofeditz, Lennart; Schmid, Leon (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Coworking Spaces (CSPs) sind geteilte Arbeitsplätze für Selbstständige, Freelancer*innen, Mikrounternehmen und Startups, die Isolation entgegenwirken und zum interdisziplinären Wissensaustausch anregen können. Jedoch existieren auch Barrieren, die Nutzer*innen davon abhalten, zu anderen Coworker*innen Kontakt aufzunehmen, da oft unklar ist, wann und ob jemand zum kreativen Austausch oder zum Anbieten von Hilfe bereit ist. Durch die Covid-19 Pandemie wurde die Unsicherheit bei der gegenseitigen Kontaktaufnahme noch weiter erschwert und viele CSPs mussten zeitweise schließen. Um Barrieren bei der Kontaktaufnahme zu reduzieren und die interdisziplinäre Zusammenarbeit zu fördern, können Informations- und Kommunikationstechnologien eingesetzt werden. Virtual Reality (VR) und Augmented Reality (AR) sind Technologien, die sich durch einen besonders hohen Grad an Immersion und sozialer Präsenz auszeichnen. Deshalb zeigen wir in diesem Beitrag, wie VR- und AR-Technologien gezielt eingesetzt werden können, um den interdisziplinären Wissensaustausch und Zusammenarbeit sowohl in CSPs als auch ortsunabhängig zu fördern. Dazu präsentieren wir positive Effekte, die durch den Einsatz einer der beiden Technologien im Zusammenhang mit CSPs erzielt werden können und leiten konkrete Gestaltungsempfehlungen für Anwendungsentwickler*innen, Unternehmen sowie Betreiber*innen von CSPs ab. Diese Gestaltungsempfehlungen basieren sowohl auf den neuesten Erkenntnissen aus der Fachliteratur als auch auf Interviews mit Expert*innen aus Forschung und Praxis mit Erfahrung im Bereich CSPs, VR und AR. Unsere Anwendungsszenarien können Entwickler*innen, Unternehmen und Betreiber*innen von CSPs als Grundlage dienen, vom Einsatz beider Technologien zu profitieren.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Banks’ tax disclosure, financial secrecy, and tax haven heterogeneity - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren

Bausteine der didaktischen Fallstudienentwicklung für die beruflichen Lehrer*innenbildung im Projekt DiPoLe - Sänger, Niklas

Besteuerung und Rechtsformwahl, 8., aktualisierte und erweiterte Auflage - Maßbaum, Alexandra; Sureth-Sloane, Caren

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

CDS investors’ risk perceptions of M&A announcements - Hippert, Benjamin; Uhde, André
We merge a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across North America and Europe with data from 5-year single-name credit default swaps (CDSs) that are written on stock-listed acquiring firms between 2005 and 2018. Subsequently, we empirically analyze the CDS investors’ risk perception of M&A announcements using event study methodologies. As a baseline finding, we provide evidence for significantly positive cumulative average abnormal CDS spread changes suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design as well as regional and sectoral differences. Moreover, results from a large variety of sensitivity analyses including deal and firm characteristics provide a deeper insight into the driving factors of CDS investors’ risk perceptions of M&A announcements.

Classifying the Ideational Impact of Information Systems Review Articles: A Content-Enriched Deep Learning Approach - Prester, Julian; Wagner, Gerit; Schryen, Guido; Hassan, Nik Rushdi (Decision Support Systems)
Ideational impact refers to the uptake of a paper's ideas and concepts by subsequent research. It is defined in stark contrast to total citation impact, a measure predominantly used in research evaluation that assumes that all citations are equal. Understanding ideational impact is critical for evaluating research impact and understanding how scientific disciplines build a cumulative tradition. Research has only recently developed automated citation classification techniques to distinguish between different types of citations and generally does not emphasize the conceptual content of the citations and its ideational impact. To address this problem, we develop Deep Content-enriched Ideational Impact Classification (Deep-CENIC) as the first automated approach for ideational impact classification to support researchers' literature search practices. We evaluate Deep-CENIC on 1,256 papers citing 24 information systems review articles from the IT business value domain. We show that Deep-CENIC significantly outperforms state-of-the-art benchmark models. We contribute to information systems research by operationalizing the concept of ideational impact, designing a recommender system for academic papers based on deep learning techniques, and empirically exploring the ideational impact of the IT business value domain.
Keywords: Ideational impact; citation classification; academic recommender systems; natural language processing; deep learning; cumulative tradition

Commentary: Opportunities and Challenges of Technology in Relationship Marketing - Steinhoff, Lena; Palmatier, R. W. (Australasian Marketing Journal)

Consumer Solidarity: A Social-System Perspective on the Glue that Holds Society Together - Alberternst, B.; Steinhoff, Lena; Eggert, A.; Giesler, M. (2021 AMA Winter Marketing Educators’ Conference Proceedings, St. Petersburg)

Corona Tracing Apps – Eine Analyse und Strukturierung des europäischen Marktes - Brendel, A.B.; Greve, M.; Masuch, K.; Trang, S. (HMD Praxis der Wirtschaftsinformatik)

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa
This study examines the relation between voluntary audit and the cost of debt in private firms. We use a sample of 4,058 small private firms operating in the period 2006‐2017 that are not subject to mandatory audits. Firms decide for a voluntary audit of financial statements either because the economic setting in which they operate effectively forces them to do so (e.g., ownership complexity, export‐oriented supply chain, subsidiary status) or because firm fundamentals and/or financial reporting practices limit their access to financial debt, both reflected in earnings quality. We use these factors to model the decision for voluntary audit. In the outcome analyses, we find robust evidence that voluntary audits are associated with higher, rather than lower, interest rate by up to 3.0 percentage points. This effect is present regardless of the perceived audit quality (Big‐4 vs. non‐Big‐4), but is stronger for non‐Big‐4 audits where auditees have a stronger position relative to auditors. Audited firms’ earnings are less informative about future operating performance relative to unaudited counterparts. We conclude that voluntary audits facilitate access to financial debt for firms with higher risk that may otherwise have no access to this form of financing. The price paid is reflected in higher interest rates charged to firms with voluntary audits – firms with higher information and/or fundamental risk.
Keywords: private firms; voluntary audit; cost of debt; self‐selection bias; risk

COVID-19 reporting and willingness to pay for leisure activities - Warkulat, Sonja; Krull, Sebastian; Ortmann, Regina; Klocke, Nina; Pelster, Matthias (Covid Economics)
The containment of COVID-19 critically hinges on individuals’ behavior. We investigate how individuals react to variations in COVID-19 reporting. Using a survey, we elicit individuals' perceived infection risk given various COVID-19 metrics (e.g., confirmed cases, reproduction rate, or case-fatality ratio). We proxy individuals' risk perception with their willingness to pay for the participation in everyday life and amusements events. We find that participants react to different COVID-19 metrics with varying sensitivity. We observe a saturation of sensitivity for several measures at critical limits used in the political discussion, making our results highly relevant for policy makers in their efforts to direct individuals to adhere to hygienic etiquette and social distancing guidelines.
Keywords: COVID-19 reporting; willingness to pay; willingness to accept

COVID-19 Reporting and Willingness to Pay for Leisure Activities - Ortmann, Regina; Warkulat, Sonja; Krull, Sebastian; Klocke, Nina; Pelster, Matthias

Curriculumforschung - Jenert, Tobias (Handbuch TransdisziplinÃ¤re Didaktik)

Customer Inertia Marketing - Henderson, C. M.; Steinhoff, Lena; Harmeling, C. M.; Palmatier, R. W. (Journal of the Academy of Marketing Science)

CYWARN: Strategy and Technology Development for Cross-Platform Cyber Situational Awareness and Actor-Specific Cyber Threat Communication - Kaufhold, M.-A.; Riebe, T.; Kühn, P.; Bayer, M.; Reuter, C.; Stöttinger, M.; Möller, R.; Mirbabaie, Milad; Fromm, J.; Basyurt, A.S.; Stieglitz, S.; Eyilmez, K.; et al. (Proceedings of the 8th Mensch und Computer)

Dark triad managerial personality and financial reporting manipulation - Mutschmann, Martin; Hasso, Tim; Pelster, Matthias (Journal of Business Ethics)

Dark Triad Personality Traits and Selective Hedging - Pelster, Matthias; Hofmann, Annette; Klocke, Nina; Warkulat, Sonja (Journal of Business Ethics)
We study the relationship between risk managers' dark triad personality traits (Machiavellianism, narcissism, and psychopathy) and their selective hedging activities. Using a primary survey of 412 professional risk managers, we find that managers with dark personality traits are more likely to engage in selective hedging than those without. This effect is particularly pronounced for older, male, and less experienced risk managers. The effect is also stronger in smaller firms, less centralized risk management departments, and family-owned firms.

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Designing a Risk Assessment Tool for Artificial Intelligence Systems - Nagbøl, Per Rådberg; Müller, Oliver; Krancher, Oliver (The Next Wave of Sociotechnical Design)

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Development of a Strategic Controlling Concept - Fiedler, Moritz

Digital Facilitation Assistance for Collaborative, Creative Design Processes - Bittner, E.; Mirbabaie, Milad; Morana, S. (54th Hawaii International Conference System Sciences)

Digital Nudging in Social Media Disaster Communication - Mirbabaie, Milad; Ehnis, C.; Stieglitz, S.; Bunker, D.; Rose, T. (Information Systems Frontiers)